The in-plane seismic response of infilled reinforced concrete frames using aStrut modelling approach: validation and applications - Messaoudi, Abdelghaffar (2024)
Reinforced Concrete (RC) buildings often rely on masonry walls to increase their rigidity and strength, distinguishing them from bare frames. Consequently, the lateral capacity of the RC frames is significantly impacted by the presence or absence of these walls. Numerical models are fundamental to understanding this behavior interaction, but the development of robust simplified models is still scarce. Based on this motivation, the reliability of a simplified numerical modelling approach was examined in this study and compared to several experimental tests. An optimized approach was implemented to determine the strut parameters, rather than relying on existing empirical formulae. The reliability of the initial stiffness, maximum strength, and energy dissipation was studied. From the results, the accuracy of the considered modelling strategy can be observed in different types of masonry elements (strong and weak units) with and without openings. The validated simulation approach reveals that the adopted macro-modelling procedure can accurately represent the behavior of infilled masonry frames. The maximum deviation of the prediction of the initial stiffness and maximum strength was found to be around 23% and 14%, respectively. These findings illustrate that the strut model effectively replicates real behavior with a satisfactory level of accuracy. However, using a consistent formula to define the strut can result in significant errors, particularly in strut width.